The role of the mast cell in pigmentation disorders - Valdemar Wendelboe Nielsen; Simon Francis Thomsen (Wolters Kluwer Medknow Publications, 2021)
The mast cell is a critical mediator of the inflammatory response by secreting histamine. While histamine is currently not regarded as a melanogen, recent studies have shown histamine release to induce melanogenesis, melanocyte proliferation and migration. Herein, we discuss the current evidence of the complex relationship between the mast cell and melanocyte, and its impact in pigmentation disorders.